Attitudes of Students on School Vegetable Garden and Gardening Activities in Kerala (Indian Journal of Extension Education, 2020)
A school vegetable garden is an innovative teaching tool and strategy that lets students incorporate hands-on activities in a diversity of multidisciplinary, standards-based lessons. The vegetable garden engages students by providing an energetic environment for them to observe, discover, experiment, nurture, and learn. The study was conducted in Thiruvananthapuram district of Kerala to identify the attitudes of students on school vegetable garden and gardening activity programme. Around 100 schools in Thiruvananthapuram are undertaking vegetable gardening in the district. Ten schools were selected for data enumeration. A total of students comprising ten students each were selected for meeting the objectives of the study. The student’s attitude was positive (60%) as a result of the influence of getting involved in school garden activities considering the mean attitude value (38.58) as a check. Age, training need, education and dwelling place were negatively correlated with attitude.